ACUTE AND SUB-CHRONIC EFFECTS OF SOME SELECTED SYNTHETIC FOOD COLORANTS ON LIVER AND KIDNEY FUNCTIONS IN ALBINO RATS (FUDMA JOURNAL OF SCIENCES, 2022)
Synthetic food colorants are widely added to food in order to attract the consumer. Many researchers have incriminated these additives for causing some problems to human health. This research was conducted to determinate the toxic effects of some selected synthetic food dyes (A, B and C) in some biochemical parameters of male albino rats in the acute test. The limit test dose of 5000 mg/kg was administered to four albino rats and then observed individually 1hour post-dosing, and at least once daily for 14 days. Sub-chronic toxicity was evaluated after administering daily oral doses of 1000, 2000, 3000 and 4000 mg/kg body weight, for 28 days to the albino rats. Results of the acute toxicity study indicated that the LD50 of the three different standard synthetic color additives (A), (B) and (C) is more than 5000 mg/kg. While in sub-chronic toxicity studies administration of synthetic food colorants, showed significant increases (P
Keywords: Albino rat, Kidney, Liver, Synthetic food colorant, Toxicity